The fractured lens: a controversial revision of the International Classification of Primary Care - Soler, Jean K.; Buono, Nicola; Cardillo, Elena; Frese, Thomas; Vinker, Shlomo; Ungan, Mehmet (Frontiers in Medicine, 2024)
Background The International Classification of Primary Care (ICPC) has represented the international standard reduction for measuring the content of primary care for over thirty years. In the process of its third revision, its authors, the Wonca International Classification Committee (WICC), delegated a major part of the technical work to a purposely formed Consortium. However, in the process of such revision, standard classification principles and rules have been inconsistently applied with the result that ICPC-3 has been published with major errors and an inconsistent structure. Objectives To formally describe and critically appraise the revision process of ICPC-3. Methods The formal review of ICPC-3 performed by an expert group within WICC and commissioned by the Executive Council of Wonca Europe is presented in abridged form. Results ICPC-3 as currently presented introduces major departures from formal classification principles and rules, besides other major errors and inconsistencies, all of which are listed and described. Conclusion Major changes in ICPC-3 defy categorisation and conceptualisation standards. ICPC-3 now represents an untested departure from international standard presentations, without a formal academic base. The direct inclusion of measures of functioning in a classification of reasons for encounter and health problems fails to address the dichotomy of these domains, the boundaries of and relationships between which are not satisfactorily resolved by the system. Analysis of ICPC-3 data will require the development and implementation of alternative, as yet undefined, models of the relationships between disease and health. By including different domains without resolving ambiguity, and by splitting function from other body systems, ICPC-3 becomes an internally fractured instrument.